Identification of Adamkiewicz artery by 4D flow MRI and intra-arterial ultra-high-resolution CT angiography in preoperative assessment of patients with chronic aortic dissection: A case report - Satoshi Higuchi, MD, PhD; Yuta Sato, MD; Hideki Ota, MD, PhD; Ryuichi Mori, RT; Yuki Ichinoseki, RT; Hitoshi Nemoto, RT; Shingo Kayano, RT; Kiichiro Kumagai, MD, PhD; Yoshikatsu Saiki, MD, PhD; Kei Takase, MD, PhD (Radiology Case Reports)
Preoperative identification of the Adamkiewicz artery (AKA) with adequate reconstruction or preservation during surgery is useful for protecting the spinal cord from ischemia during thoracoabdominal aortic repair. However, the identification of the AKA remains challenging in some cases, especially with chronic aortic dissection. In a 45-year-old man with chronic aortic dissection requiring thoracoabdominal aortic repair, conventional contrast-enhanced CT or MR angiography failed to detect AKA due to the large entry tear and an enlarged false lumen. Intra-arterial ultra-high-resolution CT angiography combined with hemodynamic assessment using 4D flow MRI successfully identified the AKA, allowing for aortic repair with targeted intercostal artery reconstruction without postoperative signs of spinal cord ischemia.